Establishment and Evaluation of HepG2 Cell Insulin Resistance Model - Meng Z; Han Y; Ruan L; Xu C; Zhang M; Liu H (Diabetes, Metabolic Syndrome and Obesity, 2025)
Zixuan Meng,1 Yuehua Han,1 Linda Ruan,1 Chenming Xu,1 Mengxiao Zhang,1,2 Hao Liu1,2 1School of Pharmacy, Bengbu Medical University, Bengbu, People’s Republic of China; 2Anhui Province Engineering Technology Research Center of Biochemical Pharmaceutical, Bengbu, Anhui Province, People’s Republic of ChinaCorrespondence: Hao Liu, Email liuhao6886@bbmc.edu.cn Mengxiao Zhang, Email zhangmx@bbmc.edu.cnObjective: Establishing HepG2 cell insulin resistance models using glucosamine, high glucose with high insulin and palmitic acid and briefly evaluating them to provide reliable models for insulin resistance research.Methods: Three methods were used to induce insulin resistance in HepG2 cells, and glucose uptake and consumption, glucose metabolism-related mRNA and p-AKT/AKT protein levels and RNA-seq were detected to compare the three induction methods.Results: Glucose consumption capacity was reduced after glucosamine and palmitic acid induction and did not change significantly after high glucose with high insulin induction. Glucose uptake capacity was not significantly changed after glucosamine and high glucose with high insulin induction and was reduced after palmitic acid induction. After high insulin stimulation, p-AKT/AKT levels were elevated in glucosamine and high glucose with high insulin induction and did not change significantly in palmitic acid induction. G6pase, PC, and PCK1 were elevated after glucosamine and palmitic acid stimulation, and only PCK1 was elevated after high glucose with high insulin stimulation. The transcriptomes of cells induced by the three methods differed widely.Conclusion: Treatment with 0.2 mM palmitic acid for 24 h is a simple and stable method to induce insulin resistance in HepG2 cells.Keywords: HepG2 cells, insulin resistance model, palmitic acid